2008
DOI: 10.1291/hypres.31.383
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Hyperreninemic Hypertension with Bilateral Positive Captopril Renography but without Renovascular Stenosis

Abstract: A 34-year-old woman was admitted to our hospital because of hypertension with hypokalemia. Her past medical history revealed that at age 24 she had been diagnosed with left renal lithiasis and had undergone extracorporeal shock-wave lithotripsy (ESWL). Physical examination showed that her peripheral pulses were intact and no peripheral edema or audible bruits were detected. Her serum potassium concentration was 2.7 mEq/mL, her plasma aldosterone concentration (PAC) was 96.7 ng/dL, and her plasma renin activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…axis functions (endocrines, circadian rhythms, etc.). It is quite possible that, similarly in similar human cases, an equivalent defective receptor mutation, also localized in chromosome 7q, translates into faulty leptin receptor causing congenital obesity [54][55][56][57][58][59][60][61][62][63][64][65][66]88,244,246,[261][262][263][264] that can influence insulin activity. 38,[54][55][56][57][58][59][60][61][62][63][64][65][66]263,264 In these human cases, demyelination defects have yet to be found and studied.…”
Section: The Myelin and Possible Causes Of The Damagesmentioning
confidence: 99%
See 1 more Smart Citation
“…axis functions (endocrines, circadian rhythms, etc.). It is quite possible that, similarly in similar human cases, an equivalent defective receptor mutation, also localized in chromosome 7q, translates into faulty leptin receptor causing congenital obesity [54][55][56][57][58][59][60][61][62][63][64][65][66]88,244,246,[261][262][263][264] that can influence insulin activity. 38,[54][55][56][57][58][59][60][61][62][63][64][65][66]263,264 In these human cases, demyelination defects have yet to be found and studied.…”
Section: The Myelin and Possible Causes Of The Damagesmentioning
confidence: 99%
“…Interestingly, the Zucker obese rats bore myelin anomalies resembling the ones found in toxicantinduced diabetes in animals [43][44][45][46][47][48][49][50][51][52] and probably also thosenot studied by fine structurefound in unusual human cases of diabetes where leptin receptor was similarly incompetent. [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] Therefore, the discussion of our demyelination data includes diabetes type 2 considerations along with leptin-linked endocrine interactions.…”
Section: Introductionmentioning
confidence: 99%
“…ACEI renogram is most cost effective if used primarily in patients with moderateto-high risk of RVH that includes abrupt or severe hypertension, hypertension resistant to 3-drug therapy, bruits in the abdomen or flank, unexplained azotemia or recurrent pulmonary edema in an elderly hypertensive patient, or worsening renal function during therapy with ACEIs. [1][2][3][4] In patients with normal or minimally reduced renal function (creatinine <1.7 mg/dL), ACEI renography has a sensitivity and specificity of about 90% for diagnosis of RVH, [1] as seen in this case.…”
Section: Introductionmentioning
confidence: 99%
“…This change results in bilateral parenchymal retention of MAG3, which is a false-positive finding of CR. [12][13][14][15] The increased intraglomerular pressure associated with diabetic nephropathy results from preglomerular capillary vasodilatation provoked by hyperglycaemia and increased postglomerular resistance which depends on vasoconstriction due to Ang II. Recent studies have suggested that renal haemodynamic responses to ACE inhibition have a wide range of interindividual variations.…”
Section: Introductionmentioning
confidence: 99%